Enantioselective Synthesis of 1‐Aryl Benzo[5]helicenes Using BINOL‐Derived Cationic Phosphonites as Ancillary Ligands. Issue 52 (22nd October 2020) - Redero, Pablo; Hartung, Thierry; Zhang, Jianwei; Nicholls, Leo D. M.; Zichen, Guo; Simon, Martin; Golz, Christopher; Alcarazo, Manuel
Abstract: The synthesis of unprecedented BINOL‐derived cationic phosphonites is described. Through the use of these phosphanes as ancillary ligands in Au I catalysis, a highly regio‐ and enantioselective assembly of appropriately designed alkynes into 1‐(aryl)benzo[5]carbohelicenes is achieved. The modular synthesis of these ligands and the enhanced reactivity that they impart to Au I ‐centers after coordination have been found to be the key features that allow an optimization of the reaction conditions until the desired benzo[5]helicenes are obtained with high yield and enantioselectivity. Abstract : A new family of α‐cationic phosphonites derived from BINOL has been synthesized. Their use as ancillary ligands in Au I catalysis allows the enantioselective assembly of 1‐aryl [5]helicenes with excellent yields and in up to 98 % ee .